Sistem Pendukung Keputusan Penentuan Calon Penerima Bantuan Program Pedagang Menggunakan Metode Evaluation Based On Distance From Average Solution - Alhamdhani Harasi; Anief Fauzan Rozi (Universitas Mercu Buana Yogyakarta, 2024)
Improving the welfare of the community is also very important because it cannot be separated from the economic aspect of the community being given a trigger by the government in the form of social assistance in the form of funds with certain objectives, for example for the benefit of traders, in creating community welfare. Of course, the government has done this, but policies regarding the provision of assistance still have to be monitored, criticized, evaluated, and developed. The services provided still include social norms to determine the process of distributing services for the merchant assistance program. In the current problem, namely regarding decision making in determining the recipients of the merchant program assistance, because currently the Dompet Duafa Institution is still determining the recipient of assistance manually. A decision support system or Decision Support System (DSS) is a system that is able to provide capabilities in terms of problem solving and communicating for a problem with semi-structured and unstructured conditions though. The basic principle of the Evaluation based on Distance from Average Solution (EDAS) method is to use two distance measures, namely Positive Distance from Average (PDA) and Negative Distance from Average (NDA). The alternative that has the highest PDA value and the lowest NDA value will be the best alternative.